Significance Of Microsilica As Active Mineral Additive In Low Water Demanding Cements - Mukhammadiyev I.A. (Genius Journals, 2023)
This article talks about low water requiring cements, which is practiced in scientific laboratories of leading scientific centers and higher educational institutions engaged in the research of mineral binders and materials based on them in the world, reducing the release of carbon dioxide gas into the environment during cement production, the use of local raw materials and industrial waste in cement production, chemical additives and mechanical a lot of scientific and research work is being carried out on the effective use of activation. In this regard, it is important to develop optimal compositions of energyefficient building materials, low-water-demanding binders that allow the economy of Portland cement clinker in cement production, using local raw materials and man-made waste, as well as surfactants, in the scientific research conducted in this regard.
Keywords: surfactants; production; chemical; research